(untitled) - Welty, Eudora (New York, NY, 1998)
This sterling collection includes an amalgam of all her longer fiction, such as The Robber Bridegroom, The Ponder Heart, and The Optimist's Daughter, as well as her complete short fiction, plus a selection of essays and autobiographical writings.
Keywords: American literature,American fiction; 20th century,20th century